Synthesis and Anticancer Activity of Rhopaladins’ Analog RPDPD Against the HeLa Human Cervical Cancer Cell Line - Chen, Feng; Wang, Hong-Mei; Kong, Ling-Qi; Chen, Qin-Hua; Ke, Li-Na; Dai, He-Liu; Zeng, Xiao-Hua (Frontiers in Chemistry, 2022)
Heterocyclic compounds were widely used in many domains; pyrrolidone is a derivative of heterocycles that can be used to synthesize anticancer drugs. A new fluorine-containing rhopaladins’ analog(E)-2-(4-bromobenzoyl)-N-(tert-butyl)-4-(4-fluoro benzylidene)-5-oxo-1-propylpyrrolidine-2-carboxamide (RPDPD for short) of 2-aroyl-4-arylidene-5-oxopyrrolidine derivative was synthesized by the one-pot synthesis method and evaluated for its anti-tumor activity in vitro via CCK8 assay and annexin V/propidium iodide (PI) staining of HeLa cells. The results exhibited that compound RPDPD has inhibited the proliferation of HeLa in a dose-dependent manner with an IC50 of 24.23 μmol/L (p < 0.05) and has low hepatotoxicity with an IC50 of 235.6 μmol/L (p < 0.05) to normal hepatocyte LO2 cells. The apoptotic assay demonstrated that compound RPDPD has induced apoptosis in HeLa cells (from 14.26 to 23.4%, p < 0.05). qRT-PCR results showed that the compound RPDPD could inhibit the expression of oncogene E6/E7 mRNA (p < 0.05) of human papillomavirus (HPV). The results of Western blot showed that the compound RPDPD promoted the expression of TIMP3 protein and inhibited the expression of MMP3 (p < 0.05). In conclusion, the compound RPDPD can inhibit the proliferation of cervical cancer cells and induce the apoptosis of cervical cancer cells, and its mechanism may be related to the inhibition of E6 mRNA and E7 mRNA expressions, and the anticancer effect of the compound RPDPD on cervical cancer is closely related to the TIMP3/MMP3 signaling axis.